Answer:
yes Cecilia make her first mistake in step 2
Answer:
<em><u>4(10+9) - 40 + 36</u></em>
<em><u>9(5+2) - 45 + 18</u></em>
<em><u>3(12+7) - 36 + 21</u></em>
Answer:
6x - 1
Step-by-step explanation:
Okay this is basically polynomial algebra:
1. Add the value of the lengths already given.
like terms: 3x + x = 4x, -4 + 2 = -2. Now you're left with, 4x - 2.
2. Find the difference between the perimeter and the sum of the lengths.
(10x -3) + (4x + 2) = 6x - 1
Answer:
2.8
Step-by-step explanation:
Answer:
#1: x = 3; #2 c = 1/2; #3 = x = 22; #4 is correct (x = -8)
Step-by-step explanation:
for the first equation everything was right until 22x = 66
after
22x = 66
you must divide everything by 22
x = 3
that is for #1
for the second equation you copied down the question wrong
the negative is still there
6c - 8 - 2c = -6
combine 6c and -2c
4c - 8 = -6
the negative remains on the 8
add 8 to both sides
4c = 2
divide 4 to both sides
c = 2/4 or just 1/2
for the third equation you must first combine like terms
-3x + 25 + x + 21 = 2
combine -3x and x & 25 and 21
-3x + x = -2x
25 + 21 = 46
-2x + 46 = 2
then subtract 46 from both sides
-2x = -44
now divide both sides by -2
x = 22
that is your answer
number four should be correct